Reading Aloud for Improving Children’s Soft Skills: A Library Research - Ni Komang Arie Suwastini; Jennet Senawati; Ni Wayan Surya Mahayanti; Ummi Kultsum; Zhu Minxia (Universitas Pendidikan Ganesha, 2025)
Although doubts may arise on the relevance of literature and reading aloud in this digital era, the present study sides with experts’ opinion that teaching aloud is an essential strategy to use literature to nurture soft skills among children. By implementing George’s model of Library research (2008), the present study critically reviews experts’ opinions and previous studies on the use of literary texts throught reading aloud for developing children’s soft skills.Using Wagner’s dimensions of soft skills, the present study reviews a total of 30 books and rticles published in reputable international journals or accredited national journals, with 25 of them published in the last ten years and 15 of them purports reading aloud for developing childfrren’s soft skills. The study reveals that listening to works of literature through reading aloud activity is argued to be beneficial for improving children’s analytical thinking, communicative, critical thinking and problem-solving skills, curiousity and imagination, and initiative. While there are not yet explicit arguments on the use of literature through reading aloud for developing children’s agility / adaptability and collaborative skills, the present study implies that reading aloud should be a regular partr of children’s exposure to literature concerning the development of their soft skills.